Diagnosis and Treatment of Emergency Abdominal Pathology at the Present Stage - Jamolovich, Kamolov Sardor; Shavkatovich, Mavlyanov Farxod (RA Journal of Applied Research, 2022)
Objective: To evaluate the effectiveness of laparoscopic diagnosis and treatment of emergency abdominal pathology. Materials and methods. An open prospective and retrospective study of clinical material was conducted using statistical and analytical methods of examination and treatment of 322 patients hospitalized in the Department of Pediatric Surgery of the Republican Scientific Center for Emergency Medical Care of the Samarkand branch in the period from 2007 to 2019. Results. As a result, this method made it possible in our clinical studies to confirm and clarify the preliminary diagnosis in 161 (50%) patients, exclude the suspected pathology before the study in 91 (28%) patients and change the diagnosis in 70 (22%) patients. Conclusions. Thus, laparoscopy allows you to reduce the percentage of unnecessary laparotomies, shorten the time of diagnosis, and reduce the occurrence of postoperative complications.